(3GdeGFI GdeSjMjI aj GdUfGYI GdWHjIs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd CHh Sgd gPG gh GdcJGH GdChd ef cJHfG aj UfGYI GdWH , hbUOfG fJcde ajeG jLH JbOjeg bHd GdTQhY aj Yde GdWH , eeG jchf eONdkG Edjg , hGddg JYGdi gh GdeYjf s
(3BNQgG (B:s
(3hjSbi GddHf hGdHbhd hGdZPjI GdQWHI hGdahGcg GQWHI hJOHj GdeGA aj CTjGA dGjYQagG , ChUHg aj Mdbg bgQkG , hPdc EPG CNP jaRY ef GdeGA abO HdZ GdJeGe aj eYfGg , hgh BNQcJHfG aj UfGYI GdWH hGdMeO dhGgH GdYbd heajV GdYOd s
(3fSNI QGHYIs
(3YdjgG hbajI ef GdTGgYHGS SfI (B1017(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B216 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B331 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs